Evaluation of several mathematical models for fitting the growth of the algae Dunaliella tertiolecta (Asian Journal of Plant Biology, 2014)
Growth curves can be found in a variety of disciplines including fishery, agriculture, biology and biotechnology. Most living matter grows with successive lag, growth, and asymptotic phases and parameters associated with these phase can be used in predictive biology. In this work we studied the growth kinetics of the algae Dunaliella tertiolecta based on available published work in the literature using several growth models such as modified logistic, modified Gompertz, modified Richards, modified Schnute, Baranyi-Roberts, Von Bertalanffy, Huang and the Buchanan three-phase linear model. Statistical analysis based on RMSE, adjusted R2, Bias Factor (BF), Accuracy Factor (AF), Akaike Information Criterion (AIC) and F-test shows mixed results with the best models implied from the statistical analysis were the Baranyi-Roberts and modified Gompertz model. The Baranyi-Roberts model was chosen to fit the growth profile of the algae under various light intensity based on its mechanistically-inclined properties. The results obtained showed that the Âµmax rose steadily from 0.317 to 1.069 (day-1) whilst the lag time were negative in values at 10 and 20 lux light intensities and steadily increased to 1.189 days at 60 lux light intensity. The results from this work can be used in the further optimization works of this alga in the future.